Water Quality Assessment of Pond Water in Jaunpur City - Prasad, Dipak; Sanyal, Srabani (National Geographical Journal of India, 2022)
Urban ecosystem services are generated in a diverse set of habitats, including: green spaces, such as parks, urban forests, cemeteries, vacant lots, gardens and yards, campus areas, landfills; and blue spaces, including streams, lakes, ponds, artificial swales, and storm water retention ponds. The wetlands, ponds, swales and trenches for water storage can encourage the biodiversity of aquatic organisms by providing a safe haven in the urban environment. Natural and manmade ponds are potential source of drinking water, ground water recharge and aesthetic beauty with their untouched view for their locality. Aquatic urban biodiversity cannot persist with anthropogenic stressors likewise an array of anthropogenic pollutants (sewage flow, solid waste, road salt and heavy metals etc.), invasive species, and active mismanagement-particularly the removal of riparian vegetation. Today growing density of household in urban areas also results confiscation of open areas, low land, pond and water bodies. Day by day areas of water bodies like ponds, lakes etc. are corrugating, which results the heavy load of sewage water and solid waste in absence of sewerage connection or negligence of waste collection in the city. India is one of the developing country having prosperous fresh water resources in the form of rivers, kunds/ponds and lakes etc. Jaunpur is an old city and is popularly known for its ponds. The rapid development, urbanization and load of the various pollutant sources lead to deterioration of ponds. The city, situated on the bank of River Gomti which bisects the city of Jaunpur (located between 25°44' to 25°46' North latitude and 82°40' to 82°43' East longitude) in the north and south directions. Population growth and urbanisation rate in the city is very high during last few decades. There are about nine to ten ponds located within the city. This study aims to investigate the physico-chemical properties and estimate WQI of some urban ponds in the ecological system of Jaunpur city which is located within the municipal area of the city.